Essential Operations Management - Hill, Alex : Terry Hill. (UK : Macmillan, Red Globe Press, 2018)
"From two highly respected authors in the field, Essential Operations Management provides a concise, student-friendly overview of operations management, striking a balance between coverage of the service and manufacturing industries that reflects current trends and supported by well-developed international case studies and learning features" --
Managing Operations -- Developing and Implementing an Operations Strategy -- Designing Services and Products -- Delivering Services -- Making Products -- Location and Layout -- Managing Capacity -- Scheduling and Executing Operations -- Managing Inventory -- Managing Quality -- Managing the Supply Chain -- Improving Operations.
Includes bibliographical references and index.
Keywords: Industrial management; Production management; BUSINESS & ECONOMICS / Production & Operations Management; BUSINESS & ECONOMICS / Operations Research; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Industries / Manufacturing Industries